2020
DOI: 10.3389/fpsyg.2020.01483
|View full text |Cite
|
Sign up to set email alerts
|

Business Environment and Entrepreneurial Motivations of Urban Students

Abstract: College students' perceptions of entrepreneurial environments exert significant influence on their entrepreneurial motivations. With China's increased focus on entrepreneurship and innovation, an increasing number of college students have embarked on a journey of self-employment and entrepreneurship. Due to disparities in the urban entrepreneurial environments, however, their entrepreneurial ventures in urban spaces are characterized by extreme phenomena such as entrepreneurial clusters and human capital fligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 47 publications
2
15
2
Order By: Relevance
“…The financial support scale was compiled by Wu and Mao (2020) , and there were five items in total. The fourth question was related to the competition intensity of local financial institutions, which had nothing to do with this study; so, it was deleted.…”
Section: Methodsmentioning
confidence: 99%
“…The financial support scale was compiled by Wu and Mao (2020) , and there were five items in total. The fourth question was related to the competition intensity of local financial institutions, which had nothing to do with this study; so, it was deleted.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that the entrepreneurial environment is a significant positive predictor of entrepreneurial intentions ( Wu and Mao, 2020 ). Essel et al (2020) have found that a good entrepreneurial environment promotes entrepreneurial intentions with empirical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Through educational design and practice, education tries to adapt to this context, and/or it will try to drive the changes and improvements that the context requires [85,86]. In particular, it has been confirmed that culture and education directly influence the intention and action to create a new venture, and indirectly through the subject's perceptions about the entrepreneurial context, in particular about the basic infrastructures for entrepreneurship [87,88]. Considering the above, the first two hypotheses state: Hypothesis 1 (H1).…”
Section: Hypotheses and Model Developmentmentioning
confidence: 99%